Front Cover: L−Lysine Amino Acid Adsorption on Zeolite L: a Combined Synchrotron, X‐Ray and Neutron Diffraction Study (ChemistryOpen 10/2020). Issue 10 (1st October 2020) - Beltrami, Giada; Martucci, Annalisa; Pasti, Luisa; Chenet, Tatiana; Ardit, Matteo; Gigli, Lara; Cescon, Mirco; Suard, Emmanuelle
Abstract : The Front Cover shows L‐lysine amino acid adsorption on zeolite L. The role of the zeolite channels in the stabilization of the lysine absorbed and the effect of water on protein structure are elucidated at atomistic level. The stabilization of the L α‐helical conformation is related to strong H‐bonds between the tail aminogroups of lysine molecules and the Brønsted acid site as well as to complex intermolecular H‐bond system between water molecules, zeolite and amino acid. More information can be found in the Full Paper by Giada Beltrami et al .